Growth Of The Tax Revenues Of Four Municipalities Of The Savannah Of Bogotá And Its Economic Transformation By The Relocation Of Industrial Activities, For The Period 2010-2016 (2016)
Comparative study on the fiscal behavior of the four most influential municipalities of the Savannah of Bogotá in the most representative period of productive and business transformation integrated with the residential and commercial sectors. In this period of observation, emphasis was placed on the different conditions conducive to the sector to provide conditions of connectivity, large areas of infrastructure development, territorial tax incentives, among others. The study will be developed in three phases: general conditions corresponding to geographic and demographic factors, recent tax behavior and income and fiscal balance demonstrated by the municipality of Chia